QOL-32. Patients treated for malignant brain tumor in the first three years of life: clinical sequelae. (3rd June 2022) - Giaquinta, Simonetta; Rossi, Bartolomeo; Pillon, Marta; Carraro, Elisa; Biffi, Alessandra; Viscardi, Elisabetta
Abstract: BACKGROUND: Pediatric Central Nervous System tumors are the most common solid tumors in children with a higher incidence rate in the first years of life. Patients treated for brain tumor are at high risk of sequelae. In the first years of life, brain immaturity increases the risk of developing these complications. OBJECTIVE: The goal of this study was to evaluate the medium and long term sequelae of malignant brain tumor treatment in patients diagnosed in the first three years of life and to correlate these sequelae with tumor histology, localization and treatment. PATIENTS AND METHODS: Forty - nine children with aggressive brain tumor diagnosed in the first three years of life followed in the Pediatric Hematology and Oncology Department of Padua between January 2000 and December 2020 were enrolled in this study. We evaluated features, such as age at onset, tumor localization, neurosurgical resection, histology, treatment and patient outocome. From May to September 2021 we clinically evaluated 16 of them who survived to treatment and we identified the presence of visual impairment, hearing loss, endocrine dysfunctions and neurological deficits in them. RESULTS: The most common sequelae in our patient population is motor impairment (30.8%), followed by endocrine dysfunction (23%), visual impairment (19.2%), epilepsy (11.6%), cranial nerve palsy (7.7%) and hearing loss (7.7%). In this study epilepsy is significantly associated with supratentorial tumors and endocrine dysfunction with high dose chemotherapy. CONCLUSIONS: Our data and recent literature confirm the high incidence of tumor and treatment sequelae in these patients. Therefore, since diagnosis, a multidisciplinary evaluation and management are necessary for improving patients' prognosis.